2008
DOI: 10.1063/1.2890448
|View full text |Cite
|
Sign up to set email alerts
|

Streamwise and spanwise plasma actuators for flow-induced cavity noise control

Abstract: Plasma actuators operating in atmospheric air can induce a body force through collisions between electrically charged particles and neutral air molecules by an externally applied electric field. The fast response and the simple structure make the plasma actuator a promising option in aerospace applications. In this work, experiments were performed with several alternative current excited plasma ͑streamwise and spanwise͒ actuators to control flow-induced noise from a cavity. It was found that the streamwise act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Roth, Sherman & Wilkinson (2000) demonstrated that these actuators can cause significant changes in friction drag on a flat plate boundary layer. This has spurred a plethora of studies, particularly in low-Reynolds-number air flows, with the aim of drag reduction (Wilkinson 2003;Jukes et al 2006b;Choi, Jukes & Whalley 2011), lift enhancement (Little et al 2010;Feng et al 2012;Greenblatt, Schneider & Schule 2012), flow separation control (Post & Corke 2006;He, Corke & Patel 2009;Schatzman & Thomas 2010), vortex shedding control (Thomas, Kozlov & Corke 2008;Jukes & Choi 2009a,b,c), transition control (Grundmann & Tropea 2008;Hanson et al 2010) and noise control (Huang & Zhang 2008). Further information on operating principles and flow control applications can be found in the review articles by Moreau (2007), Corke, Post & Orlov (2009) and Wang et al (2013).…”
Section: Dbd Plasma Flow Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Roth, Sherman & Wilkinson (2000) demonstrated that these actuators can cause significant changes in friction drag on a flat plate boundary layer. This has spurred a plethora of studies, particularly in low-Reynolds-number air flows, with the aim of drag reduction (Wilkinson 2003;Jukes et al 2006b;Choi, Jukes & Whalley 2011), lift enhancement (Little et al 2010;Feng et al 2012;Greenblatt, Schneider & Schule 2012), flow separation control (Post & Corke 2006;He, Corke & Patel 2009;Schatzman & Thomas 2010), vortex shedding control (Thomas, Kozlov & Corke 2008;Jukes & Choi 2009a,b,c), transition control (Grundmann & Tropea 2008;Hanson et al 2010) and noise control (Huang & Zhang 2008). Further information on operating principles and flow control applications can be found in the review articles by Moreau (2007), Corke, Post & Orlov (2009) and Wang et al (2013).…”
Section: Dbd Plasma Flow Controlmentioning
confidence: 99%
“…Chan, Zhang & Gabriel (2007) and Huang & Zhang (2008) used DBD-VGs for noise control upstream of a rectangular cavity. The streamwise vortices impeded development of organized structures within the cavity, which disrupted the fluidacoustic feedback mechanism to reduce the aerodynamic noise.…”
Section: Dielectric-barrier-discharge Vortex Generatorsmentioning
confidence: 99%
“…It was shown that longitudinal vortices were induced by the jets and cavity tone was suppressed effectively. As shown in the previous research [1][2][3][4], it is revealed that upstream flow control was effective to reduce the cavity tone. However, reduction mechanism of cavity tone and effects of spacing of jets on cavity flow has not been clarified.…”
Section: Introductionmentioning
confidence: 98%
“…There have been many attempts to reduce the cavity tone by various methods such as plasma actuators, synthetic jets and blowing jets [1,2]. Huang et al [3] attempted to control cavity tone by plasma actuators in the upstream boundary layer and investigated the effects of the direction of the plasma actuators on suppression of the cavity tone. It was shown that streamwise plasma actuators, which spanwisely induced flow, were more effective in the noise reduction than a spanmwise plasma actuator.…”
Section: Introductionmentioning
confidence: 99%
“…DBD plasma actuators have been used for separation control of aerofoils (Corke et al 2010(Corke et al , 2011Whalley et al 2013), vortex shedding control of bluff bodies (Munska and McLaughlin 2003;McLaughlin et al 2004;Jukes and Choi 2009), delaying laminar-to-turbulent transition (Grundmann and Tropea 2007) and noise reduction of cavity flows (Huang and Zhang 2008). Wilkinson (2003) created a spanwise flow oscillation in the turbulent boundary layer with DBD plasma actuators by applying a frequency modulating input to a pair of lower electrodes on either side of an upper electrode.…”
Section: Transverse Wall Motionsmentioning
confidence: 99%